Written in Skin: SuicideGirls - Christiansen, Steen (Nordlit, 2009)
Suicidegirls.com is a website which is both an online community, but also a softcore pin-up site, where the models feature extensive body modifications in the form of tattoos and piercings. The website promotes a democratic approach to the photo shoots, as the models remain in control, not the photographer. Marked by their body modifications, the Suicide Girls (as they call themselves), they actively attempt to subvert the typical pin-up conventions, by transgressing mainstream standards of beauty. In what seems remarkably similar to Judith Butler's account of subversive bodily acts, the pin-up shoots of the Suicide Girls mount a critique of a culture's view of the body as a natural entity. Cultural borders are crossed, as the bodies of the Suicide Girls embed ink into their bodies in the form of tattoos, and gender is played as a subversive game against the expectations of pin-up conventions. Acting as different and impure bodies, the Suicide Girls represent a threat to conventional conceptions of the body.
Keywords: Tattos; Body Modifications; Pin-ups; Gender; Subversion; Transgression; Subculture